The value of serum albumin level as a predictor of the incidence of hypertensive disorders in pregnancy at Samawa Province - Al-Silaykhee, Wurood Mahdi (International Journal of Psychosocial Rehabilitation, 2020)
The aim of this research is to determine the seriousness of preeclampsia based on serum albumin levels. Methodology: According to their blood pressure, 100 women were split into four groups: regulation (n=22), gestational hypertension (n=25), moderate preeclampsia (n=29), and extreme preeclampsia (n=24). Concerned regarding the serum albumin amounts of each woman being compared. In addition, race, gestational age, parity, systolic blood pressure, and diastolic blood pressure were both taken into account. When serum albumin levels are compared between the classes, there is a substantial difference (p0.05). The age gap between control and extreme preeclampsia is substantial (p=0.04), according to the results. There was a statistically significant gap in gestational age between the control and other groups (p0.05), as well as a statistically significant difference in systolic and diastolic blood pressure between the groups (p0.05). Conclusion: In moderate and extreme preeclampsia, serum albumin levels are lower than in usual and hypertensive conditions, according to this report.